Hydrogen-Rich Saline Promotes the Recovery of Renal Function after Ischemia/Reperfusion Injury in Rats via Anti-apoptosis and Anti-inflammation - Li, Jie; Hong, Zhijian; Liu, Hong; Zhou, Jihong; Cui, Lei; Yuan, Siming; Chu, Xianghua; Yu, Pan (Frontiers in Pharmacology, 2016)
Purpose: Hydrogen is a proven novel antioxidant that selectively reduces hydroxyl radicals. In this study, we investigated the effects of hydrogen-rich saline solution on the prevention of renal injury induced by ischemia/reperfusion (I/R) and on renal function recovery. Methods: A rat model of renal I/R injury was induced by 45 min occlusion of the left renal pedicle, followed by 108 h reperfusion. The right kidney was surgically removed. Then, 0.9% NaCl solution (1 ml/kg) or hydrogen-rich saline solution (HRSS) (1 ml/kg) was injected into the abdominal cavity at four hours intervals. We assessed the influence of HRSS or control saline solution on the recovery of renal function after I/R injury. Kidney tissues were taken at different time points (24, 36, 48, 72 and 108 h after reperfusion) and frozen (-80˚C). Kidney cell apoptosis was evaluated using terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive staining. Additionally, the apoptotic factors (Bcl-2, Bax, caspase-3, caspase-9 and caspase-8) and the pro-inflammatory cytokines (IL-6 and TNF-α) were measured in the kidney tissues. Finally, serum blood urea nitrogen (BUN) and creatinine (Cr) levels were measured. Results: Histological analyses revealed a marked reduction of interstitial congestion, edema and hemorrhage in renal tissue after HRSS treatment compared to saline treatment. After I/R injury, BUN, Cr, Bcl-2, caspase-3, caspase-9, caspase-8, IL-6 and TNF-α were all significantly increased, while Bax expression was decreased. HRSS remarkably reversed these changes. Moreover, BUN and Cr decreased more rapidly in the rats treated with HRSS compared to the rats treated with control saline solution. Conclusions: HRSS showed a protective effect in the prevention of renal injury and could promote renal function recovery after I/R injury in rats. HRSS might partially exert its role through an anti-apoptotic and anti-inflammatory action in kidney cells.